2014
DOI: 10.3892/br.2014.315
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the serum fibrin-fibrinogen degradation products with cytokeratin 19 fragment as biomarkers in patients with lung cancer

Abstract: Abstract. Lung cancer is one of the main causes of cancer-related mortality. The identification of early diagnostic biomarkers improved outcomes for lung cancer patients. Serum fibrin-fibrinogen degradation products (FDP) levels are elevated in numerous malignancies due to hemostatic alterations. The serum FDP levels were compared to the levels of cytokeratin 19 fragment antigen (CYFRA 21-1), another well-established biomarker. The serum samples from 193 lung cancer patients, 84 healthy controls and 106 patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…Genetic and proteomics-based biomarkers are two major types of biomarkers, which can be identified through tumor cells, urine, sputum, blood, or other body fluids [ 3 ]. Table 3 demonstrates numerous lung cancer markers [ 121 , 122 , 123 , 124 , 125 , 126 , 127 , 128 , 129 , 130 , 131 , 132 , 133 , 134 , 135 , 136 , 137 , 138 , 139 , 140 , 141 ].…”
Section: Biomarkers For Lung Cancer Detectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Genetic and proteomics-based biomarkers are two major types of biomarkers, which can be identified through tumor cells, urine, sputum, blood, or other body fluids [ 3 ]. Table 3 demonstrates numerous lung cancer markers [ 121 , 122 , 123 , 124 , 125 , 126 , 127 , 128 , 129 , 130 , 131 , 132 , 133 , 134 , 135 , 136 , 137 , 138 , 139 , 140 , 141 ].…”
Section: Biomarkers For Lung Cancer Detectionmentioning
confidence: 99%
“…Many types of proteomic biomarkers have been investigated for lung cancer detection, including Annexin II [ 122 ], APOA1 [ 123 ], carcinoembryonic antigen (CEA) [ 124 ], carbohydrate antigen 125 (CA125) [ 125 ], carbohydrate antigen 19-9 (CA19-9) [ 126 ], cytokeratin fragment 21-1 (CYFRA21-1) [ 127 ], CD59 glycoprotein [ 128 ], transthyretin (TTR) [ 129 ], GM2 activator protein (GM2AP) [ 130 ], haptoglobin-R2 [ 131 ], Ig-free light chain [ 132 ], neuron-specific enolase (NSE) [ 133 ], nitrated ceruloplasmin [ 134 ], plasma kallikrein B1 [ 135 ], ProGRP [ 136 ], retinol binding protein (RBP) [ 137 ], squamous cell carcinoma (SCC) [ 138 ], vascular endothelial growth factor (VEGF) [ 139 ], TPA [ 140 ], and tumor M2-pyruvate kinase [ 141 ].…”
Section: Biomarkers For Lung Cancer Detectionmentioning
confidence: 99%
“…Fibrin degradation products (FDPs) have been described as angiogenic [ 37 ]. Previous studies have shown fibrin degradation products are elevated in lung, ovarian and a variety of gastrointestinal cancers and have shown potential to be used as biomarkers [ 38 , 39 , 40 , 41 ]. VC has been shown to activate the coagulation system and to increase fibrin deposition in hepatic tissue [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…The early studies clarified that in malignant stages of lung cancer, CYFRA 21-1 is released into the blood circulation of patients and elevated in their serum [3]. Therefore, it is possible to improve the survival of lung cancer patients by early detection and consequently fast surgical reaction [4].…”
Section: Introductionmentioning
confidence: 99%